PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays Saccharata Sturt) DENGAN PEMBERIAN BEBERAPA JENIS BAHAN ORGANIK - Sitorus, Ramli; Lufita Nur Alfiah; Rizah Rizwana Wahyuni (SUNGKAI, 2023)
Sweet corn Zea mays Saccharata Sturt is a food crop commodity that is in high demand because it contains carbohydrates The most important factor in increasing sweet corn production is improving soil nutrients by fertilizing The purpose of this study was to determine the effect of several types of organic matter on the growth and production of sweet corn This research was conducted at the Kassa House of the Faculty of Agriculture University of Pasir Pengaraian in Rokan Hulu Regency Riau Province from March to May 2022 This research was carried out using a Completely Randomized Design CRD method with 4 treatments P0 Without Addition of Organic Materials P1 75g solid plant P2 75g empty oil palm bunches tankos plant P3 75g rice husk plant The parameters in this observation were plant height number of leaves leaf width leaf length corn weight and level of sweetness sweetness but significant effect on corn weight parameters The P2 treatment 75 g of tankos plant tended to give the highest value on the parameters of the number of leaves leaf width and corn weight.